Introduction To Elementary School Building 070978 Gunungsitoli With 3d Animation Using Hybrid Method: Introduction To Elementary School Building 070978 Gunungsitoli With 3d Animation Using Hybrid Method - Wa'asaro Telaumbanua; Fauziah Fauziah; Ratih Titi Komala Sari (Institute of Computer Science (IOCS), 2020)
The development of the animation film industry is growing very rapidly and is characterized by the many works of Aimasi in various media. Visual motion shooting in animation is essential for creating a character that moves realistically, in an impractical or too dangerous situation. To get the motion shot in animation is still very minimal because the availability of equipment and technology implementation in the world of animation is still very expensive both in terms of equipment and software used. The expected result in this research is making a video of SD Negeri 070978 Gunungsitoli Building with the perspective of 3D animation can make the school building animation and can support students to better understand the location of the schools building, and can be an introductory material module to promote to foreign parties and can obtain realistic visual motion and shorten the time of animating in the making of 3D animation films.